Pola Komunikasi Interpersonal Antar Pustakawan Dan Pemustaka Dalam Meningkatkan Kualitas Pelayanan Pada Perpustakaan Universitas Hindu Negeri I Gusti Bagus Sugriwa Denpasar - Wayan Ngurah Eka Kurniawan (Pramana: Jurnal Hasil Penelitian, 2023)
The library is a work unit in the form of a place for collecting, storing and maintaining library material collections that are managed and systematically arranged in a certain way, to be used sustainably by users as a source of information. Good library management can support education and the learning process in higher education, with good communication patterns it will have an impact on the quality of service at the library. Universitas Hindu Negeri I Gusti Bagus Sugriwa is a university that has just changed its status to a university in 2020. Based on this formulation, the theories used to dissect the formulation of the problem are: (1) Communication Planning Theory, (2) Discourse Theory, and (3) Social Action Theory. This research took place in the library of Universitas Hindu Negeri I Gusti Bagus Sugriwa. The type of research used is qualitative, with the determination of informants using purposive sampling method. Collecting data using observation methods, interviews with guidelines assisted by voice recorder research tools and cellphones, literature and documentation. Data analysis carried out in this study used data reduction, data presentation, and data verification. The findings of this study, namely in its implementation, the existence of librarians in establishing communication with users using verbal and non-verbal communication patterns in providing information to users so that users make it easier to find library materials in the library of Universitas Hindu Negeri I Gusti Bagus Sugriwa Denpasar, will have an impact on the quality of existing resources, Libraries in service to users use an open management system in serving users where users look for library materials on library shelves according to the field they are involved in.